Determinants of foreign direct investment and its implications on tax revenue in Indonesia - Suparna Wijaya; Ayu Kusuma Dewi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study aims to examine the effect of market size, trade openness, inflation rate, political stability, corruption, population, and status of human capital on tax revenue with Foreign Direct Investment (FDI) as an intervening variable. This research is quantitative research with a multiplier linear regression model. The sample used in this study includes the provinces in Indonesia. The sample was carried out from 2014 to 2019 using a purposive sampling method, resulting in 180 observations. The research model was tested using two-panel data regression models, namely FEM – GLS Heteros and Autoregressive and Random Effect models (REM). The results show that: 1) market size, trade openness, and the level of human capital have a positive effect on FDI inflows; 2)market size, trade(openness), inflation rate, corruption level, population, human capital level, and Foreign Direct Investment (FDI) have a positive effect on tax revenue; and 3) market size (market size), trade (openness), and the level of human resources (human capital) have an indirect effect on tax revenue through Foreign Direct Investment (FDI).